Einfluß von Hyperund Hypothyreose auf den Energiestoffwechsel der Skelettmuskulatur - Moka, D.; Theissen, P.; Linden, A.; Waters, W.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 1991)
31P magnetic resonance spectroscopy allows non-invasive evaluation of phosphorus metabolism in man. The purpose of the present study was to assess the influence of hyper- and hypothyroidism on the metabolism of resting human skeletal muscle. The present data show that quantitative measurement of phosphate metabolism by NMR is possible as also demonstrated by other studies. Using a quantitative evaluation method with an external standard, significant differences in the levels of phosphocreatine, adenosintriphosphate, and phosphodiesters were found. In hypothyroid patients a TSH-dependent increase in phosphodiesters and a decrease in adenosintriphosphate and phosphocreatine was observed. In hyperthyroidism a similar decrease in adenosintriphosphate but a considerably higher decrease in phosphocreatine occurred. In the light of the results of other studies of muscle metabolism, these changes appear to be non-specific so that further studies are required to assess the clinical value of such measurements.